QUIZIZZ EFFECTIVENESS IN IMPROVING STUDENT`S VOCABULARY MASTERY AT MA ULUL ALBAB MAKASSAR - Muhammad Chairil Imran; Sulviana Sulviana; Hendrianto Tuajo (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
This study aims to evaluate the effectiveness of using Quizizz in improving students' vocabulary mastery at MA Ulul Albab Makassar, particularly for 10th-grade students in the Science (IPA) and Social Sciences (IPS) classes. The research questions addressed are as follows: (1) Can the use of Quizizz effectively enhance students' vocabulary mastery at MA Ulul Albab? (2) Are students interested in using Quizizz for learning English? A quantitative method with a pretest-posttest single-group design was employed in this study. The research instruments included tests and interviews. The sample consisted of two classes, namely, 10th-grade students in the IPA and IPS streams. Data collection was conducted through tests, classroom interaction observations, and documentation. The results of the study showed that the pretest and posttest scores were 48.7097 and 82.8710, respectively, indicating a significant improvement in students' vocabulary mastery after using Quizizz. Based on the survey results, Quizizz was proven to be effective in enhancing students' understanding of vocabulary at MA Ulul Albab. The interactivity and challenging game elements of this platform made students more interested and actively engaged in the learning process. The statistical analysis using the Paired Samples Test table indicated that the Sig. (2-tailed) value was 0.000 < 0.05, thus rejecting H0 and accepting Ha. Therefore, it can be concluded that there is a significant difference in the average scores between the Pre Test and Post Test, indicating that the Quizizz application effectively enriches the English vocabulary of 10th-grade students in the IPA and IPS streams at MA Ulul Albab Makassar.